PENGARUH KONSENTRASI ETANOL TERHADAP AKTIVITAS ANTIBAKTERI EKSTRAK DAUN LILI PARIS (Chlorophytum comosum) - Dany Hexa Grosny Ralphsody; Lindawati, Novena Yety (Universitas Pekalongan, 2025)
Staphylococcus aureus is a pathogenic bacterium that frequently causes serious infections, such as skin infections, pneumonia, and sepsis. The increasing resistance to conventional antibiotics has prompted the search for alternative therapies derived from natural sources. Spider plant (Chlorophytum comosum) leaves are known to contain bioactive compounds such as flavonoids, saponins, and terpenoids, which have potential antibacterial properties. This study aims to determine the effect of varying ethanol concentrations (40%, 70%, and 96%) on the antibacterial activity of spider plant leaf extracts against Staphylococcus aureus. Extraction was carried out using the maceration method with ethanol solvents at concentrations of 40%, 70%, and 96%. Each extract underwent phytochemical screening. Antibacterial activity was tested using the well diffusion method against Staphylococcus aureus ATCC 25923. The inhibition zones were measured using a caliper. Data were analyzed using normality and homogeneity tests, one-way ANOVA, and Tukey’s post hoc test. Phytochemical screening results showed that the 40% ethanol extract contained only flavonoids and tannins, while the 70% and 96% ethanol extracts contained flavonoids, terpenoids, tannins, and saponins. Antibacterial testing showed that the 70% ethanol extract produced the largest inhibition zone (9.75 mm), followed by the 96% ethanol extract (7.25 mm), and the 40% ethanol extract (6.3 mm). ANOVA results indicated significant differences between groups (p < 0.05), and the post hoc test showed that the 70% ethanol extract differed significantly from the other two groups. Ethanol 70% was the most effective solvent for extracting antibacterial compounds from spider plant leaves, as it produced the highest antibacterial activity against Staphylococcus aureus. These results support the potential use of spider plant leaf extract as a natural antibacterial candidate.